NATIONAL DIRECTORATE OF EMPLOYMENT BASIC NATIONAL OPEN APPRENTICESHIP SCHEME TRAINEES’ RATINGS OF THEIR EMPLOYABILITY IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study determined National Directorate of Employment Basic National Open ApprenticeshipScheme trainees’ ratings of their employability in Anambra State. Two research questions andtwo null hypotheses guided the study. The descriptive survey design was adopted. All thepopulation, which was 240 NDE B-NOAS 2021 trainees from three Local Governments inAnambra State, was used as the sample. A 63-item questionnaire was used for data collection,which were validated by three experts. Test re-test reliability method was employed, andPearson Product Moment Correlation Co-efficient was used to determine the reliability of theinstrument, which yielded an overall co-efficient of 0.87. Mean and standard deviation wereused to answer the research questions, while analysis of variance (ANOVA) was used to test thehypothesis. The findings revealed that NDE B-NOAS trainees possessed high technical and ICTskills after their training for employability in Anambra State. There was a significant differencein the mean ratings of graduates of tertiary institutions and school leavers of lower level ofeducation on their technical skills and ICT skills for employability after NDE B-NOAS trainingin Anambra State. It was, therefore, concluded that that adoption of technical skills and ICTskills will go a long way to increase the quality of manpower and reduce the rate unemploymentor dependence on government for job. Based on the findings, it was recommended among others,that effective instructional technique and strategies should be adopted by trainers to achieveemployability skills necessary for the world of work for their trainees.
Keywords: Unemployment, National Directorate of Employment, Basic National Open Apprenticeship Scheme, Employability